2012
DOI: 10.1007/s13311-012-0123-z
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Interventions for ADHD: A Neurodevelopmental Perspective

Abstract: It is proposed that the time is ripe for the development of secondary preventive interventions for attentiondeficit/hyperactivity disorder (ADHD). By targeting preschool children, a developmental stage during which ADHD symptoms first become evident in most children with the disorder, many of the adverse long-term consequences that typify the trajectory of ADHD may be avoided. A dynamic/ interactive model of the biological and environmental factors that contribute to the emergence and persistence of ADHD throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
95
2
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(105 citation statements)
references
References 95 publications
0
95
2
8
Order By: Relevance
“…Halperin et al [95,96] and Sonuga-Barke and Halperin [97] have proposed that it is possible to prevent or alter the trajectory of ADHD in preschool children through a program of activities focusing on cognitive and motor skills (for more detail see Halperin and Healey [98]), which targets the underlying pathology associated with the dual pathway model. Halperin et al [95] demonstrated improvement on parent-and teacher-rated ADHD symptom scales for preschoolers with ADHD who underwent a program training a variety of executive functioning skills, including attention, inhibition, working memory, planning, visuospatial, and motor skills. The improvement was maintained at a follow-up period 3 months later.…”
Section: Developmental Considerations For Cognitive Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Halperin et al [95,96] and Sonuga-Barke and Halperin [97] have proposed that it is possible to prevent or alter the trajectory of ADHD in preschool children through a program of activities focusing on cognitive and motor skills (for more detail see Halperin and Healey [98]), which targets the underlying pathology associated with the dual pathway model. Halperin et al [95] demonstrated improvement on parent-and teacher-rated ADHD symptom scales for preschoolers with ADHD who underwent a program training a variety of executive functioning skills, including attention, inhibition, working memory, planning, visuospatial, and motor skills. The improvement was maintained at a follow-up period 3 months later.…”
Section: Developmental Considerations For Cognitive Trainingmentioning
confidence: 99%
“…Recent research has provided evidence of this assertion as cognitive training also targeting self-control has yielded improvements in ADHD symptoms both at home and in the classroom environment in young children [95]. How well the changes in performance or neural functioning associated with cognitive training relate to the generalization of training effects is unknown and an important area of study.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…This has been supported by Halperin and colleagues who studied an intervention that had the aim of addressing the array of neurodevelopmental disorders that are consistent with ADHD (32)(33)(34)(35)(36).…”
Section: Introductionmentioning
confidence: 92%
“…Such approaches would target early signs of difficulty, to prevent the onset of the full disorder and its escalation to more complex presentations (Halperin, Bedard, & Curchack‐Lichtin, 2012). Longitudinal studies commencing in preschool suggest that there is a significant degree of developmental continuity associated with early hyperactivity (Kan et al., 2013).…”
Section: Introductionmentioning
confidence: 99%